A Study on Speech within the Marriage Ceremony of the Luwu Community, South Palopo in Basse Santempe (Bastem) - Andi Nur Hayati (Fakultas Sastra - Universitas Muslim Indonesia, 2019)
The purpose of this study describes and interpreting form act said, acts said dominant way act speech and function act said used in ceremony custom wedding society of Bastem. This research was conducted in Bastem, Luwu, South Sulawesi Province. The method used is the descriptive method where made ​​a systematic description and rules about the data studied. The descriptive method chosen for the research conducted aims to describe clearly the object under study naturally. Of research findings obtained in that form of speech acts traditional wedding ceremony in Bastem form of action how about the courtesy and understanding of customary law which must be carried out and implemented in life, especially the marriage ceremony, the next speech acts are dominant in the marriage ceremony is from the woman's speech act grateful love, explain and asked, while on the men which speech acts grateful. Then the speech acts are spoken in the marriage ceremony that is by polite, careful and respectful in public bastem wedding ceremonies, and the last speech acts are used in traditional wedding ceremony bastem society serves as a speech act aimed at the women and men with accompanying speech acts goal was spoken. To achieve a deeper study suggested enrich linguistic, contribute in preserving the indigenous communities Bastem, as well as reviewing the speech act of birth and death ceremonies, create archives by reference in observing the development of time-backward.